17.8k views
4 votes
What are the steps to get from the og equation (black) to its inverse (red)?

What are the steps to get from the og equation (black) to its inverse (red)?-example-1
User Meatballs
by
4.5k points

1 Answer

6 votes

Given the function f(n) defined below:


f(n)=-6n+1

To find its inverse, we follow the steps below:

Step 1: Replace f(n) with y.


y=-6n+1

Step 2: Swap y and n.


n=-6y+1

Step 3: Solve for y.


\begin{gathered} 6y=-n+1 \\ y=(-n+1)/(6) \end{gathered}

Step 4: Replace y with the inverse function.


f^(-1)(n)=(-n+1)/(6)

These are the required steps to get the inverse function.

Alternate Method


\begin{gathered} n-1=-6y \\ (n-1)/(-6)=y \end{gathered}

Bring the negative to the upper part.


\begin{gathered} (-(n-1))/(6)=y \\ y=(-n+1)/(6) \end{gathered}

User Wabbitseason
by
4.8k points